The Year-End Trading Activities of Institutional Investors: Evidence from Daily Trades - Hu, Gang; McLean, R. David; Pontiff, Jeffrey; Wang, Qinghai (Review of Financial Studies, 2014)
At year-end, some allege that institutional investors try to mislead investors by placing trades that inflate performance (portfolio pumping) or distort reported holdings (window dressing). We contribute direct tests using daily institutional trades and find that year-end price inflation derives from a lack of institutional selling rather than institutional buying. In fact, institutional buying declines at year-end. Consistent with pumping, institutions tend to buy stocks in which they already have large positions. We find no evidence of window dressing, as institutions are not more likely to buy high-past return stocks or sell low-past return stocks at year- or quarter-end.